Anti-Inflammatory and Antioxidant Properties of the Ethanol Extract of Clerodendrum Cyrtophyllum Turcz in Copper Sulfate-Induced Inflammation in Zebrafish - Thu Hang Nguyen; Hong Diep Le; Thanh Nguyen Thi Kim; Hai Pham The; Thi Mai Nguyen; Valérie Cornet; Jérôme Lambert; Patrick Kestemont (MDPI AG, 2020)
Oxidative stress and inflammation are commonly present in many chronic diseases. These responses are closely related to pathophysiological processes. The inflammatory process can induce oxidative stress and vice versa through the activation of multiple pathways. Therefore, agents with antioxidant and/or anti-inflammatory activities are very useful in the treatment of many pathologies. Clerodendrum cyrthophyllum Turcz, a plant belonging to the Verbenaceae family, is used in Vietnamese traditional medicine for treating migraine, hypertension, inflammation of the throat, and rheumatic arthritis. Despite its usefulness, studies on its biological properties are still scarce. In this study, ethanol extract (EE) of leaves of C. cyrtophyllum showed protective activity against CuSO4 toxicity. The protective activity was proven to relate to antioxidant and anti-inflammatory properties. EE exhibited relatively high antioxidant activity (IC50 of 16.45 µg/mL) as measured by DPPH assay. In an in vivo anti-antioxidant test, three days post fertilization (dpf) zebrafish larvae were treated with different concentrations of EE for 1 h and then exposed to 10 µM CuSO4 for 20 min to induce oxidative stress. Fluorescent probes were used to detect and quantify oxidative stress by measuring the fluorescent intensity (FI) in larvae. FI significantly decreased in the presence of EE at 5 and 20 µg/mL, demonstrating EE’s profound antioxidant effects, reducing or preventing oxidative stress from CuSO4. Moreover, the co-administration of EE also protected zebrafish larvae against oxidative damage from CuSO4 through down-regulation of hsp70 and gadd45bb expression and upregulation of sod. Due to copper accumulation in zebrafish tissues, the damage and oxidative stress were exacerbated overtime, resulting in the upregulation of genes related to inflammatory processes such as cox-2, pla2, c3a, mpo, and pro- and anti-inflammatory cytokines (il-1ß, il-8, tnf-α, and il-10, respectively). However, the association of CuSO4 with EE significantly decreased the expression of cox-2, pla2, c3a, mpo, il-8, and il-1ß. Taken together, the results suggest that EE has potent antioxidant and anti-inflammatory activities and may be useful in the treatment of various inflammatory diseases.